Contemporary review of exercise in heart transplant recipients - Guimarães, Guilherme Veiga; Ribeiro, Fernando; Arthuso, Fernanda Zane [UNESP]; Castro, Rafael Ertner; Cornelissen, Véronique; Ciolac, Emmanuel Gomes [UNESP] (Elsevier, 2021)
Heart transplantation (HTx) is a therapeutic option for a selected group of patients with end-stage heart failure. Although secondary prevention including exercise therapy is recommended in the management of patients following HTx, little information is available on their metabolic and physiological consequences in HTx. Therefore, we aimed to conduct a contemporary review the effectiveness of exercise therapy on functional capacity, cardiovascular health and health-related quality of life for adult HTx patients. We searched the database MEDLINE for articles published between January 2015 and October 2020 and were able to include 6 studies involving 202 patients. Larger improvements in exercise capacity were seen after high-intensity interval training and in patients with evidence of cardiac reinnervation. Clinically relevant reductions were observed for daytime and 24 h ambulatory blood pressure after exercise training and following a single bout of aerobic exercise. Finally, limited data suggest that quality of life is higher in HTx patients following high-intensity training. In summary, the available evidence shows the potential for exercise as a vital treatment in patients following HTx. Yet, the scant data calls for more well-designed and adequately powered studies to support its effectiveness and to unravel optimal exercise characteristics, which would allow for more effective and person-tailored exercise prescription.
Keywords: Cardiac rehabilitation; Exercise; Heart transplantation; Physical activity